2015
DOI: 10.5125/jkaoms.2015.41.1.52
|View full text |Cite
|
Sign up to set email alerts
|

An unusual abscess formation in the masticator space after acupressure massage: a case report

Abstract: Clinical features of masticator-space abscess (MSA) are very similar to those of parotitis or temporomandibular disorder (TMD), making early differential diagnosis difficult. Local causes of MSA include nerve block anesthesia, infection after tooth extraction, and trauma to the temporomandibular joint (TMJ); the systemic cause is immunodeficiency. Odontogenic causes account for most etiologies, but there are also unusual causes of MSA. A 66-year-old male patient visited the emergency room (ER) presenting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Patients with masticator space abscesses were different in both groups, as most masticator space abscesses were caused by the degree dental care. 23 This group of patients had the same characteristics as patients with care, including masticator space abscess patients who could not open their mouths. This was a serious concern of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with masticator space abscesses were different in both groups, as most masticator space abscesses were caused by the degree dental care. 23 This group of patients had the same characteristics as patients with care, including masticator space abscess patients who could not open their mouths. This was a serious concern of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ko et al reported a case with abscess formation in the masticator space after acupressure massage, which was initially diagnosed as TMD. After CT imaging and needle aspiration, the treatment focused on MSI and the patient's symptoms improved [4]. Matsumura et al also presented a case with peritemporomandibular abscess as a complication of acupuncture [7].…”
Section: Discussionmentioning
confidence: 99%
“…The masticator space, a collective term for the superficial and deep temporal, submasseteric, and pterygomandibular spaces, is confined by the masticator muscles including the temporalis, masseter, lateral, and medial pterygoid muscles [4]. Masticator space infection (MSI), which is mostly caused by the spread of odontogenic infection, may present as TMJ pain, masticator muscle tenderness, or trismus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Knowledge of precise localization of purulent content is crucial for decisions regarding surgical intervention. 1 There is a bunch of literary sources [2][3][4][5] which describe diverse aspects of diagnostics and management of purulent head and neck conditions, but not enough number of articles [6][7][8] , presenting a profound description of ultrasound (US) images in those patients. And even many fewer studies focus on ultrasound upon infection of masticatory space.…”
mentioning
confidence: 99%